Andreev reflection at a NS interface for non-normal angle of incidence - R. Hoonsawat (2018)
The Andreev reflection of electrons at a NS (normal-superconductor) interface is studied for the case where the angle of incidence is not normal. It is seen that the deviation of the Andreev reflection coefficient (for E > Δ) from ideal Andreev reflection. increases as the angle of incidence and that the deviation becomes greater as the mismatch at the interface is increased. © 1988.